The Effect of Antepartum Yoga Sequences on Anxiety Levels, Vital Sign Values, and Fetal Heart Rate in Third-Trimester Primigravida - Reni Yuli Astutik; Noor Pramono; Hardhono Susanto; Martha Irene Kartasurya (Jurnal Ilmu Kesehatan Masyarakat, 2022)
Anxiety in the third-trimester pregnancy can affect the physical and psychological aspects of the mother and fetus. Until now, there has been no study comparing yoga sequences that are effective in reducing anxiety levels in third-trimester primigravida. The yoga sequence will cause the heart rate to return to normal after finishing exercising, and the body will feel more comfortable. This study aims to determine the effect of antepartum yoga sequences on anxiety levels, vital sign values, and fetal heart rate in third-trimester primigravida. This study was quasi experiments with a pretest posttest control group design conducted in January-April 2022. The sampling technique used cluster sampling to determine the intervention group and control group. The intervention group was given antepartum yoga sequences for six sessions with a duration of 60 minutes, consisting of 18 respondents in A group model and 18 respondents in B group model. The control group consisting of 18 respondents, received pregnancy exercise for six sessions with a duration of 60 minutes. Data analysis using T-test. The results showed differences in the control group for anxiety (p-value = 0.042), pulse (p-value = 0.021) and respiratory frequency (0.032). In the intervention group model A, there were differences in anxiety, diastolic blood pressure, pulse, and respiratory rate with p-values ​​of 0.032, 0.005, 0.005, and 0.005, respectively. While in the intervention group model B, there were significant differences in anxiety, systolic blood pressure, diastolic blood pressure, pulse, respiratory rate, and fetal heart rate, namely p-values ​​of 0.005, 0.002, 0004, 0.005, 0.005, 0.005. The results of this study can be used by midwifery service providers as one of the complementary treatments for reducing anxiety experienced by third-trimester primigravida mothers, namely by giving antepartum yoga, which is done for 60 minutes.